DESAIN PONDASI TIANG RAKIT DENGAN METODE POULOS DAN SOFTWARE PLAXIS - I Nyoman Sutarja; I Wayan Redana; I Made Putra Dwityagana (JURNAL SPEKTRAN, 2019)
DESIGN OF RAFT-PILE FOUNDATION BY POULOS METHOD AND SOFTWARE PLAXIS ABSTRACT In Bali, especially Kuta area there are many layers of soft soil with hard soil depth far from the surface of the land. Sufficient foundation design is required to avoid soil degradation. This research aims to produce alternative pole-raft foundation design using Poulos manual method and Plaxis software. Poulos manual method using trial and error method with variation dimension cross section of pile, pile length, and number of piles. The results of this study show the final design configuration of the alternative foundation of this raft pile has a thickness of 0.30 meters raft and 25x25 cm2 pile along the 7 meters with 20 pieces. From this ideal configuration obtained the calculation of soil yield calculation by Poulos method of 6,53 cm, while with Plaxis software of 6,92 cm. Percentage mobilization of ultimate capacity of pole system with Poulos method by 52%, while using Plaxis software 56,5%. The percentage of load borne by the pole system by Poulos method is 79,83%, while with Plaxis software 80,24%.